Instructional skills improvement plan (ISIP) for music teachers in the elementary level - Tamayo, Nariza T. (Laoag City : [s.n.], 2018)
This study proposed an instructional skills improvement plan for music teachers in the elementary level in the three schools divisions of Ilocos Norte namely: Division of Ilocos Norte, Division of Laoag City and Division of the City of Batac. The instructional skills improvement plan was anchored on Maquizo's institutional planning theory and the System's Theory, in relation to the K to 12 Curriculum Model. This research utilized the research and development (R&D) methodology which was undertaken in three major stages: the planning stage which included a bibliographical survey of related literature and an empirical survey of the status of music education which determined the profile, the level of knowledge and skills of the music teachers in the different aspects of instruction, and their problems and concerns; the development of the improvement plan, and its validation by experts. Data were gathered through the administration of a questionnaire to 230 music teachers and conduct of interviews with school administrators.
Bibliography: pages 202-206.
CHED-La Union
Keywords: Music teachers; School music